Observations on Predators of Giant Clams (Bivalvia: Family Tridacnidae) - Alcazar, Sally (Silliman Journal, 2024)
Giant clams are now the subject of mariculture studies throughout the Indo-Pacific region (Gwyther and Munro, 1981; Fitt et al., 1984; Heslinga and Watson, 1985). One question to be answered before large-scale culture is attempted is the extent of predation in the natural habitats. This paper presents preliminary observations on predation on five species of tridacnids (Tridacna crocea [Lamarck], T. derasa [Réding], T. maxima [Réding], . squamosa [Lamarck] and Hippopus hippopus [Linn.]) in the laboratory and in nature.